The impact of breastfeeding on health and the economy - Mehyeddine, IKHLEF Fahed; Mohamed, SALI (The journal of contemporary issues in business and government, 2023)
This research deals with the impact of breastfeeding on health and the economy, by addressing the statement of the concept of breastfeeding, its definition, types and effects on the child and on breastfeeding as well, and the second element we have devoted to explaining what is meant by the impact of breastfeeding on the economy by addressing some details related to artificial breastfeeding through a statement of its definition and impact on the child as well as the impact of breastfeeding and artificial feeding on the economy. We have reached a set of results, including: that breast milk is the ideal food for the baby, as it provides all the nutrients necessary for healthy growth, and economically, it saves money for the purchase of milk and a bottle of milk, as well as the expenses of treatment of various diseases that can affect the infant who is fed with formula.